Curious George takes a vacation and discovers new things - Welker, Frank; Bennett, Jeff, 1945-; Macy, William H., 1950-; Rey, Margret; Rey, H. A. 1898-1977 (Hans Augusto) (Universal City, CA : Universal Studios Home Entertainment, 2008)
The Man with the Yellow Hat and George have several vacation adventures.
Curious George takes a vacation -- Unbalanced -- The times of sand -- Curious George takes a dive -- Sea monkey -- Curious George sees stars -- Curious George and the missing piece -- Castle keep.
Based on the books by Margret and H.A. Rey.
Features: star shapes game, 8 printable coloring pages, 8 connect-the-dots.
Voices: Frank Welker, Jeff Bennett, Annie Mumolo, Jim Cummings ; William H. Macy, narrator.
Originally broadcast on PBS Kids television in 2007.
TV rating: Not rated.
DVD, Dolby digital surround.
Keywords: Rey, Margret -- Film and video adaptations; Rey, H. A. -- 1898-1977 -- Film and video adaptations; Curious George (Fictitious character) -- Juvenile films; Human-animal relationships -- Juvenile films; Vacations -- Juvenile films; Curious George (Fictitious character) -- Drama; Human-animal relationships -- Drama; Vacations -- Drama; Television programs for children; Children's films; Video recordings for the hearing impaired; Fiction television programs; Television programs; Fiction television programs; Television programs; Based on the book; Animated television programs